The rules of the game: discursive norms and limits in the field of online art magazines. Issue 2 (15th March 2021) - Soro, Tommie; Stott, Tim; O'Rourke, Brendan K.
ABSTRACT: This article employs methods of discourse analysis and corpus linguistics within a Bourdieusian theoretical framework to examine the discursive norms and limits regulating the construction of reputation by online contemporary art magazines. Moving between quantitative and qualitative analysis of the websites of online contemporary art magazines, the article identifies salient patterns surrounding the use of modifiers and links these patterns to the normative principles of the artworld. Its findings suggest that positive evaluation is a norm but that the use of explicitly evaluative modifiers is prohibited, that artists are predominantly classified according to nationality and that these classifications can construct reputational value by performing agents' possession of cosmopolitan capital. These findings contribute to our understanding of the discursive means by which artworld hierarchies and systems of classification are reproduced and transformed. Thus, this study aims to contribute to our understanding of the role of discourse in the artworld's reputational economy.